2020
DOI: 10.3390/scipharm88010014
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein/ABCB1 Might Contribute to Morphine/Cisplatin-Induced Hepatotoxicity in Rats

Abstract: To investigate combined effect of the anticancer drug cisplatin (CP) and the opiate analgesic morphine (MOR) on liver, rats were administered MOR (10 mg/kg/day i.p. for 10 days), with or without CP (7.5 mg/kg i.p. once at day 5 of the study). MOR or CP alone caused deterioration of liver function tests and induced damage to histological architecture of liver. In addition, each drug alone caused hepatic oxidative stress, as evident by significant increase of malondialdehyde and nitric oxide, as well as the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our histopathological findings demonstrated that CIS administration caused various degenerative alterations in the liver cells of normal rats, which supports the biochemical evidence of oxidative stress. 46 Hepatocytes are known to accumulate substantial amounts of CIS, so the toxicity in hepatocytes is attributed to CIS storage. 47 These changes were reduced when FA, LDR, or both were applied with CIS.…”
Section: Discussionmentioning
confidence: 99%
“…Our histopathological findings demonstrated that CIS administration caused various degenerative alterations in the liver cells of normal rats, which supports the biochemical evidence of oxidative stress. 46 Hepatocytes are known to accumulate substantial amounts of CIS, so the toxicity in hepatocytes is attributed to CIS storage. 47 These changes were reduced when FA, LDR, or both were applied with CIS.…”
Section: Discussionmentioning
confidence: 99%